Reflections and contributions to the debate on the origin of the discipline of International Relations - Velázquez Flores, Rafael (2024)
The purpose of this paper is to contribute some ideas to the debate on the origin of the International Relations discipline. The argumentative line of the essay is that, due to the enormous impact of the First World War, the discipline of International Relations emerged formally, independently, and with its own identity, starting in 1919. In this sense, the essay states that the revisionists have not taken into account, with the necessary depth, the effect that this conflict had on establishing that date as the official appearance of this discipline. The text is divided into four parts. The first seeks to clarify the difference between the terms international relations and International Relations. The second part discusses the first studies linked to global affairs before 1919. The third part discusses the formal emergence of the discipline. The last section of the text explains the development and consolidation of the discipline after the Second World War.